Pengaruh Model Pembelajaran Contextual Teaching And Learning (CTL) terhadap Minat dan Hasil Belajar Siswa Kelas X di MA Darul Falah Bendiljati Sumbergempol dalam Mata Pelajaran Sejarah - Putri Divana Nur Rohmah; Dita Hendriani (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This research is based on the situation of students who lack enthusiasm when learning and tend to be passive. The objectives of this research are To determine the effect of ctl learning model on students' interest and learning outcomes in social studies subjects in X grade MA Darul Falah. This research uses a quantitative approach with a Quasy Experimental Design type of experiment and the research design used is a posttest-only control group design. The population in this study were all X grade students at MA Darul Falah. The sample for this study was 30 control class students and 23 experimental class students. The sampling technique used was purposive sampling. Data collection uses student learning interest questionnaires and student learning achievement tests. Data analysis in hypothesis testing uses the T test, namely the Independent Sample T-Test and MANOVA Test. From the results of this study, it can be seen that the time token learning model has an effect on students' interests and learning outcomes as evidenced by the sig. (2-tailed) value of 0.000 < 0.05. the implications of this study show that the use of the ctl learning model can increase student interest.